Research of a Hybrid Diesel Locomotive Power Plant Based on a Free-Piston Engine - Serhiy Buriakovskyi; Borys Liubarskyi; Artem Maslii; Danylo Pomazan; Tatyana Tavrina (Communications - Scientific letters of the University of Zilina, 2020)
This article describes one of the possible ways for improving the energy efficiency of shunting diesel locomotives. It means a replacing a traditional traction electric transmission with a diesel generator set with a hybrid transmission with a free-piston internal combustion engine and a linear generator. The absence of a crankshaft in an internal combustion engine makes it possible to reduce thermal and mechanical losses, which, in turn, leads to an increase in the efficiency of traction electric transmission of the diesel locomotive.